2016
DOI: 10.1371/journal.pone.0154322
|View full text |Cite
|
Sign up to set email alerts
|

How Live Performance Moves the Human Heart

Abstract: We investigated how the audience member’s physiological reactions differ as a function of listening context (i.e., live versus recorded music contexts). Thirty-seven audience members were assigned to one of seven pianists’ performances and listened to his/her live performances of six pieces (fast and slow pieces by Bach, Schumann, and Debussy). Approximately 10 weeks after the live performance, each of the audience members returned to the same room and listened to the recorded performances of the same pianists… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
36
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 24 publications
2
36
0
2
Order By: Relevance
“…Little research has examined differences between live and recorded performances by manipulating the presence and absence of the performer. Shoda et al (2016) reported that the heartbeats of audience members at a live performance exhibited greater entrainment with the musical rhythm than those of listeners at a pre-recorded performance. Performer presence was also found to produce greater relaxation in audience members compared to those listening to a recording (Shoda et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Little research has examined differences between live and recorded performances by manipulating the presence and absence of the performer. Shoda et al (2016) reported that the heartbeats of audience members at a live performance exhibited greater entrainment with the musical rhythm than those of listeners at a pre-recorded performance. Performer presence was also found to produce greater relaxation in audience members compared to those listening to a recording (Shoda et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Shoda et al (2016) reported that the heartbeats of audience members at a live performance exhibited greater entrainment with the musical rhythm than those of listeners at a pre-recorded performance. Performer presence was also found to produce greater relaxation in audience members compared to those listening to a recording (Shoda et al, 2016). Contemporary popular performers often play variations of recorded works at live performances (Shoda and Adachi, 2015), suggesting a novelty factor for listeners.…”
Section: Introductionmentioning
confidence: 99%
“…Here we collected physiological responses from several individuals simultaneously as they listened to a live organ concert in a naturalistic environment. We chose a live concert design because listening to live music has been shown to yield superior entrainment between music and body physiology, compared to recorded music (Shoda et al, 2016 ), which in turn is likely to maximize the chances of inter-individual synchronization to occur. We took advantage of the possibility of using one of the most versatile organs available in Europe, capable of imitating a large number of musical instruments.…”
Section: Introductionmentioning
confidence: 99%
“…Being in the context of a concert in the presence of other people can enhance the listening experience by eliciting at least a rhythmic synchronization when people move together (Desmet et al, 2010). Live conditions provide listeners with the strongest musical experiences (Lamont, 2011), with a greater effect on physiological variables as heart rate (Shoda et al, 2016). However, contradictory results have emerged from several studies.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, to study interpersonal synchronization and the mechanisms involved in social interactions, it is possible to simulate research protocols that are as realistic as possible whilst maintaining ecological validity. Ecological experiments in the musical context have already measured head movement synchronization by simulating a live concert in a living lab (Swarbrick et al, 2019), or measured the heart rate of a few people among a large audience listening to a piano performance in an auditorium (Shoda et al, 2016). Otherwise, when natural settings are not reproducible in ecological conditions, it is possible to benefit from the specific design arising from a natural situation.…”
Section: Introductionmentioning
confidence: 99%